CHALLENGES IN THE IMPLEMENTATION OF INCLUSIVE EDUCATION AT ELULAKENI CLUSTER PRIMARY SCHOOLS IN SHISELWENI DISTRICT OF SWAZILAND - Adebayo, Awoniyi Samuel; Ngwenya, Karen (European Scientific Journal, ESJ, 2015)
The purpose of the study was to find out the challenges in the implementation of Inclusive education at Elulakeni Cluster primary schools in the Shiselweni District of Swaziland. The research employed the descriptive or survey research design. The population of the study consisted of 14 primary schools with 14 head teachers and seventy grades one to five teachers all of which were used for the study. A questionnaire of 33 items of the five point Likert scale was used to collect data. The instrument was face and content validated and the reliability determined using the Cronbach’s Alpha reliability method. An Alpha reliability coefficient of 0.655 was obtained for the instrument. The collected data was coded and analyzed using the descriptive statistics and factor analysis. The study revealed that eleven factors accounted for 76.426% variance in challenges in the implementation of Inclusive education. These are: teachers’ competency; material and financial resources; teachers’ friendliness, efficacy of administration; classroom environment; human resources; collaboration, productive responses to classroom challenges, fairness to all students; playing materials and spacious classrooms. Of these, teachers’ competency; material and financial resources; teachers’ friendliness, efficacy of administration were major challenges in the implementation of Inclusive education at Elulakeni Cluster primary schools in the Shiselweni District of Swaziland and these were either often or sometimes challenges as indicated by the overall means. Based on the findings, it was therefore recommended that the Ministry of Education (MOE) should consider training of administrators and teachers on Special Education needs and that the Government review the allocation of funds for Inclusive Education by increasing budgetary provisions to cater for the required resources in all schools.